External assessor of the candidates who applied for a faculty position at the rank of Assistant Professor at the Hellenic Military Academy - Tsapatsoulis, Nicolas (My University, 2026)
External assessor of the candidates who applied for a faculty position at the rank of Assistant Professor at the Hellenic Military Academy